The Synoptic Problem Where to from here? - Monaghan, Christopher John (2017)
The study of the Synoptic Problem continues with a wide range of hypotheses proposed to explain the relationship of Mark, Matthew and Luke to the early Jesus tradition, and to each other. This article reviews recent developments in synoptic studies highlighting the recognition of the ongoing role of the oral tradition, the ways in which scribal compositional practices in the first century have been used to test the major hypotheses, and the methodological constraints that accompany research in this area.
Keywords: Q Source; Synoptic Problem; composition practice; minor agreements; Oral Tradition